2021
DOI: 10.21873/invivo.12420
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Esterase and Glucose Reagent Test Can Rule in and Rule out Septic Arthritis

Abstract: Background/Aim: Septic arthritis (SA) requires rapid diagnosis and therapy to avoid joint damage. This study evaluated the diagnostic accuracy of leukocyte esterase (LE) and glucose (GLC) strip tests for diagnosing SA. Patients and Methods: Synovial fluids from 455 patients with atraumatic joint effusions were assessed prospectively over a 5-year period with LE and glucose strip tests. Results were compared to modified Newman criteria for diagnosing joint infections. Synovial fluid cultures, crystal, blood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
4
1
2
Order By: Relevance
“…Omar et al, were among the first to investigate the joint evaluation of LE and glucose with the reagent strip test as a diagnostic approach for the diagnosis of SA. In contrast to our data, the authors reported that simultaneous measurement of glucose and LE improved diagnostic accuracy and increased the positive predictive value from 34.6% to 94.4%, with no significant impact on test sensitivity and negative predictive value [ 5 ]. Apart from the fact that Omar et al, analyzed test performance in native joints, no detailed information on participant characteristics was available to explain the variance in synovial glucose and LE apart from septic reasons.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Omar et al, were among the first to investigate the joint evaluation of LE and glucose with the reagent strip test as a diagnostic approach for the diagnosis of SA. In contrast to our data, the authors reported that simultaneous measurement of glucose and LE improved diagnostic accuracy and increased the positive predictive value from 34.6% to 94.4%, with no significant impact on test sensitivity and negative predictive value [ 5 ]. Apart from the fact that Omar et al, analyzed test performance in native joints, no detailed information on participant characteristics was available to explain the variance in synovial glucose and LE apart from septic reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the data previously published by Parvizi et al, the LE values “-” and “+” were considered as negativity cut-off [ 11 ]. With respect to glucose concentration, no change of color at the test pad represented a diminished amount of glucose in the synovial fluid [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors describe techniques that provide supportive evidence for a diagnosis of sepsis such as cytological examination of fluid, total protein concentrations, synovial fluid serum amyloid A concentrations and glucose concentration. In humans, a recent study demonstrated encouraging patient side results using test strips for semi-quantitative analysis of leucocyte esterase and glucose concentrations in joint fluid from suspected septic arthritis patients presenting for emergency care (Kolbeck et al 2021). This interesting application requires only a small drop of fluid.…”
mentioning
confidence: 99%
“…In humans, a recent study demonstrated encouraging patient side results using test strips for semi‐quantitative analysis of leucocyte esterase and glucose concentrations in joint fluid from suspected septic arthritis patients presenting for emergency care (Kolbeck et al . 2021). This interesting application requires only a small drop of fluid.…”
mentioning
confidence: 99%